Disintermediation as a Brand in the Banking Sector: Essence and Peculiarities of Manifestation - Baymuratova M.T. , (European Journal of Life Safety and Stability (2660-9630), 2023)
The article discusses the essence of disintermediation in the banking sector and the features of its manifestation in developed and developing countries, formulates the conditions necessary for the effective implementation of intermediary functions by financial institutions.